Effects of drought stress and subsequent rewatering on photosynthetic and respiratory pathways in Nicotiana sylvestris wild type and the mitochondrial complex I-deficient CMSII mutant - Galle, Alexander (Journal of experimental botany, 2010)
The interaction of photosynthesis and respiration has been studied in vivo under conditions of limited water supply and after consecutive rewatering. The role of the alternative (v(alt)) and cytochrome (v(cyt)) pathways on drought stress-induced suppression of photosynthesis and during photosynthetic recovery was examined in the Nicotiana sylvestris wild type (WT) and the complex I-deficient CMSII mutant. Although photosynthetic traits, including net photosynthesis (A(N)), stomatal (g(s)) and mesophyll conductances (g(m)), as well as respiration (v(cyt) and v(alt)) differed between well-watered CMSII and WT, similar reductions of A(N), g(s), and g(m) were observed during severe drought stress. However, total respiration (V(t)) remained slightly higher in CMSII due to the still increased v(cyt) (to match ATP demand). v(alt) and maximum carboxylation rates remained almost unaltered in both genotypes, while in CMSII, changes in photosynthetic light harvesting (i.e. Chl a/b ratio) were detected. In both genotypes, photosynthesis and respiration were restored after 2 d of rewatering, predominantly limited by a delayed stomatal response. Despite complex I dysfunction and hence altered redox balance, the CMSII mutant seems to be able to adjust its photosynthetic machinery during and after drought stress to reduce photo-oxidation and to maintain the cell redox state and the ATP level